Influence of parental involvement on student’s academic achievement in public mixed day secondary schools in Yatta Sub-County, Machakos County - David, Dominic Muthami (Strathmore University, 2022)
Research shows that parental involvement in schools is closely linked to better student behavior, higher academic achievement and enhanced social skills. The influence of parental involvement on student’s academic achievement can be investigated through various forms. However, the forms of involvement that have the strongest effect on the student's academic achievement are not clear. Based on varying forms of parental involvement, different scholars have drawn different findings and conclusions with some concluding that there exists no relationship between parental involvement and academic achievement. This study sought to advance the investigation of the influence of parental involvement in academic achievement in mixed-day secondary schools in Yatta sub-county, Machakos County. Specifically, it focused on the influence of parental involvement on supervision of the learner's homework, communicating expectations and target setting, and participation in school activities. The study adopted Bronfenbrenner’s ecological systems theory focusing on the Micro-system, Meso-system, Exo-system and Macro-system. Data was collected using questionnaires and interviews. The study sampled 15 schools from 29 public mixed-day secondary schools in the sub-county. The study also targeted school principals, Class teachers, Form Three parents and Form Three students of the sampled schools. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) version 28, while the qualitative data were analyzed using thematic analysis. There was a significant positive correlation between homework supervision and academic achievement, the communication of expectations together with target setting and that academic achievement, and finally, the participation in school activities and academic achievement. The study established that parental involvement is positively influencing academic achievement. The study recommends the formulation of a policy framework that provides guidance and direction in reference to parental involvement. The strategy will guide and enhance homework taking, create links with parents to provide the necessary information, and motivate students to take homework. Further research can be done to establish the reason why many schools did not have a school policy on parental involvement and other socioeconomic factors influencing parental involvement.
A Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Education Management at Strathmore University
Keywords: Parental involvement; Student’s academic achievement; Public mixed day secondary schools_Yatta Sub-County, Machakos County